Community violence and reactive and proactive aggression: the mediating role of cognitive and emotional variables/ violencia comunitaria y agresión reactiva y proactiva: el papel mediacional de las variables cognitivas y emocionales/ violência ... (2012)
Children exposed to higher levels of violence tend to be more aggressive. Specific mechanisms explaining this relationship are still being uncovered. This study sought to identify the relationship between exposure to community violence and reactive and proactive aggression, as well as cognitive and emotional variables mediating this relationship. Participants were 1,235 students (from fifth to ninth grade) from localities of Bogotá, Colombia, with varying levels of community violence. Analyses of self-reported measures confirmed significant associations between exposure to community violence and both reactive and proactive aggression. Normative beliefs supporting aggression, hostile attribution of intent, positive expectations for aggression, and lack of guilt after aggression, partially mediated these relationships, suggesting strategies for prevention.